STATISTICAL COMMUNICATION PARAMETERS OF LUNAR SEISMIC EVENTS ON EARTH - Vyzhva, S.; Kazancev, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A statistical comparison of seismic phenomena for 2001–2011 ys with some parameters of the Moon's orbit was carried out. There were obtained some significant dependences of the seismic phenomena quantity on the Earth upon the Moon's parameters. It was make a conclusion that the Moon is differently influenced on the seismic phenomena quantity which occur at different depths (up to 40 km and deeper then 40 km).